Bioactive Performances of Surface Modification of Ti–6Al–4V Jointly Using Ultrasonic‐Assisted Microarc Oxidation and Hydrothermal Treatment. Issue 12 (2nd August 2022) - Xu, Cheng; Chen, Liang-Yu; Zheng, Chuanbo; Zhang, Zheng-Yi; Li, Ruifeng; Yang, Hong-Yu; Peng, Jinhua; Zhang, Lina; Zhang, Lai-Chang
Abstract : With the aim of further enhancing the bioactive performance of Ti–6Al–4V, ultrasonic‐assisted microarc oxidation (MAO) and hydrothermal (HT) treatments are combined to produce denser, more uniform hydroxyapatite (HA) crystals on the MAO coating herein. More Ca elements can be deposited on the coating and more TiO2 can be generated to form a thicker coating via ultrasonic assistance. Meanwhile, the MAO coating with ultrasonic assistance avoids the appearance of heterogeneous areas and homogenizes the distribution of elements. Those positive effects of ultrasonic‐assisted MAO coating provide favorable conditions for the subsequent HT treatment to form dense and uniform HA crystals. In vitro experiment shows that the ultrasonic‐assisted MAO coating has a higher number of MG63 cells compared with other samples. Moreover, the formation of HA crystals improves the biological activity of all samples. In the ultrasonic‐assisted sample after HT treatment, denser and more uniform HA crystals on the coating surface result in the higher alkaline phosphatase activity of the sample. Abstract : With the aim to enhance the bioactivity of Ti–6Al–4V, ultrasonic‐assisted micro‐arc oxidation and hydrothermal treatment are combined to produce denser, more uniform hydroxyapatite (HA) crystals on the micro‐arc oxidation coating. The micro‐arc oxidation coating with ultrasonic assistance avoids the appearance of heterogeneous areas and homogenizes the distribution of elements. The formation of HA crystals improves the bioactivity of all samples.